Albania Fiscal Policy: Designing Tax Policy by Given Circumstances - Kadiu, Fatbardha (Mediterranean Journal of Social Sciences, 2012)
I will consider through this paper the fiscal policy that Albania has applied in the recent years. First I will give anoverview of macroeconomic situation in Albania. After that I will describe an overview of what tax system looks like in Albania, Iwill discuss the principle objective that Albania may attempt to achieve through the tax policy. I will conclude by considering thepolitical economy environment within which tax policy and economic growth must be designed and implemented. The aim of thepaper is to set out some of the basic problems facing tax policy in Albania and to outline some key element that should beconsidered in designing the best feasible tax structure for the particular circumstances at this particular time in Albania.